Yield stability of common bean genotypes in the state of Santa Catarina, Brazil - Baldin, Rafael Carlos; Kavalco, Sydney Antonio Frehner; Woyann, Leomar Guilherme; Rodrigues Junior, Adão Alves; Gobatto, Debora Regiane; Silva, Gabriela Rodrigues da; Benin, Giovani; Finatto, Ticiane (Pesquisa Agropecuaria Brasileira, 2021)
The objective of this work was to evaluate the grain yield and stability of common bean genotypes, as well as the representativeness and discrimination ability of locations in multi-environment trials (METs), using the GGE biplot analysis. The grain yield of 27 genotypes was evaluated in 16 trials carried out in nine locations, in the state of Santa Catarina, Brazil, during the first and second crop seasons of 2014/2015 and 2015/2016. A randomized complete block design with three replicates was used. As the trials were neither conducted in all locations, nor in all growing seasons of both years, a highly unbalanced dataset was used. Genotype 5 (CHC 01-175-1) was the most productive and stable, common bean genotype and can be considered the closest one to the ideal for the target region. Furthermore, this genotype performs well in both crop seasons, outperforming all the evaluated checks; therefore, it has the potential to be released as a new cultivar. Chapecó can be considered the ideal location for the selection of common bean genotypes, in the state of Santa Catarina, since it shows high representativeness and discrimination ability in the rainy and dry crop seasons.